Section: Technology and Management Topics of Interest Section: Operations Research Controlling Corporate Working Asset Management - Gryzunova N.V.; Khvostova А.А.; Pyatanova V.I; Shuvalova E. B. (Communications of International Proceedings, 2021)
The relevance of this study is due to the need to search for optimal approaches and tools for the formation and management of circulating assets in the financial management system of modern economic entities. Controlling the management of circulating assets, which is one of the most important areas of fi - the accounting policy of the company and which is the key financial process in general. This is due to the constant transformation of the types and types of assets and their ability to provide solvency and liquidity. In addition, current assets are subject to the action of conjunctural changes in the commodity and financial markets. The aim of this work is to consider the analytical, legal and methodological aspects of current asset management in the financial management system of corporations. Objectives of the article - present the methodological aspects of building an effective system for managing circulating assets. The object of the study is the financial management system of corporations. The subject of the study is methodological approaches and tools for the formation and management of circulating assets. However, from the point of view From the point of view of financial management, current assets can pose a threat to the company in the event of inflationary processes, moral impairment, natural loss. The effectiveness of the organization as a whole depends on the management of current assets. In this regard, it is worth noting that the efficiency of managing current assets in economic entities has a direct impact on the indicators of their profits and profitability. The article considered a list of the most common tools for the effective management of current assets in the financial management system of Russian corporations.
Keywords: Controlling; Current Assets; Accounts Receivable; Stocks; Investments; Tools; Capital; Management; VAT; Calculations; Funds; Management.